STUDY ANALYSIS OF PRECAST PIER PERFORMANCE OF MULTISPAN LRT STRUCTURE USING LEAD RUBBER BEARING WITH NON LINEAR TIME HISTORY ANALYSIS - Abdurrahman Shiddiq, Husain
Currently, conventional reinforced concrete bridge structures are still used as a choice of structural systems. Then it takes longer time on the construction period and the pier as a place for energy dissipation so that the pillar will be damaged, but this system has good ductility. To speed up the construction period, a Precast Segmental Bridge Column (PSBC) system will be reviewed, but this system has poor ductility, so this configuration is designed as a “strong connection” with the help of Lead Rubber Bearings as the main energy dissipator. The purpose of this study is to study the seismic performance of PSBC configuration with LRB, seeking between the pier and LRB, which are dominant in dissipating earthquakes and pier conditions will be plastic or elastic. By comparing 2 study parameters, namely using LRB and without using LRB. The LRT structure was first designed in accordance with ACI 343 standards for guideway and earthquake loading using SNI 2833, for base isolation using AASHTO GSID. The concept of design is that pier remains elastic when the earthquake is 1000 and 50 years, while for LRB it remains elastic at 50 years but may melt when 1000 years. Then perform a performance analysis with the Non Linear Time History Analysis, each given 7 pieces of 50 annual earthquakes and 1000 annual earthquakes to be taken on average. Based on the non-linear analysis, the structure using LRB remained elastic (<IO) while without using LRB experienced (LS), due to period shifts due to addition of damping from LRB.